Sprint performance in rugby players: A systematic review - Turiman, Sharul Nizam; Ahmad, Zulkifli; Johari, N. H. (Springer, 2022)
The purpose of this review is to summarize the recent research that has examined the sprint performance and training of rugby players at different playing standards. Research articles published between 2010 and 2020 in PubMed, Science Direct and OATD were searched using key terms related to rugby player and sprint movement. Twenty related articles investigating sprint performance in both men and women players were included. Sprinting training were differently assessed using GPS device, timing gate, high speed camera, stopwatch and performance profiler database (PPD). Back rugby players were recorded sprint faster than forward players with the average of 1.69 s ± 0.06 s for 10 m sprint. On top of that, professional back rugby players logged longer sprint distance in 15 side rugby game for male (353.0 ± 147.0 m) and 7 side rugby game both male (168.0 ± 88.2 m) and female (133.0 m) player. Comparative analysis in terms of sprint performance between professional and amateur players were also presented. The sprint performance recorded in this review will be useful as the benchmark and guide for rugby training strategy at different playing standards. Future studies should investigate the factors likely to influence the player sprinting performance, especially on the technique and skills.